Peripheral Immunophenotype in the Diagnosis of Mesenteric Ischemia in Rats: An Experimental Study - Aydin Eray Tufan; Pinar Yazici; Elif Tufan; Anil Akkus; Ozlem Ton Eryilmaz; Ufuk Oguz Idiz; Fatih Ozcelik; Cemal Kaya (Journal of Investigative Surgery)
Aim Acute mesenteric ischemia (AMeI) is a mortal intestinal emergency with vascular origin. Mortality and morbidity can be prevented by early diagnosis and prompt intervention. In this study, an AMeI rat model was established to investigate the efficacy of immunophenotyping to reveal a biomarker of AMeI.Material and methods Twenty-one adult female Sprague-Dawley rats were divided into three groups. In the Sham group (Group 1), after laparotomy, the superior mesenteric artery (SMA) was found, and no further intervention was performed. In the ischemia-reperfusion group (Group 2), SMA was occluded only for 45 min whereas in Group 3(ischemia group), SMA was permanently occluded. Peripheral blood mononuclear cells were quantified for T cell subsets using flow cytometry.Results Regarding hematological biomarkers, only mean platelet volume (MPV) values in Group 3 were significantly higher compared to Group 2 (p = 0.0134). Platelet lymphocyte ratio values and D dimer levels were higher in Group 3 compared to the sham Group (p = 0.0219, p = 0.0012; respectively). No statistically significant difference was detected between groups considering the subtypes of lymphocytes surface antigens. However, in the correlation matrix analysis, significant correlations were observed between Chiu histopathological stage of ileum mucosa and CD45+ and CD4 + CD8 + [Spearman r = 0.571 (95% CI: 0.172-0.809) p = 0.0068 and Spearman r = 0.4908 (95% CI: 0.061-0.767) p = 0.0239]. Likewise, a positive linear correlation was found between MPV, D-dimer and Chiu score [Spearman r = 0.5155 (95% CI: 0.094 − 0.780; p = 0.0168) and r = 0.7828 (95% CI: 0.520 − 0.910; p < 0.0001), respectively].Conclusion Blood levels of CD45+ and CD4 + CD8+ were proved to be higher in study groups. Remarkable positive linear correlation with histopathological changes may also play a predictive role to investigate the role of these markers in larger samples.